Utilization of marine diatom Thalassiosira weissflogii as a feed additive in seawater-tolerant Nile tilapia (Oreochromis niloticus, Linnaeus 1758) strain - Huervana, Fredson H.; Dionela, Cleresa S.; de la Torre, Eirene Dorothy S.; del Castillo, Carmelo S.; Traifalgar, Rex Ferdinand M. (Frontiers in Sustainable Food Systems, 2022)
The use of marine diatom Thalassiosira weissflogii as a dietary additive in the seawater Nile Tilapia strain was evaluated. One hundred ninety-two, 1.40±0.05g seawater tilapia strains were randomly allocated into 4 treatment groups in 4 replicates. The first treatment group was fed with a control diet, without the diatoms while treatments 1, 2, and 3 were each fed with diets supplemented with T. weissflogii at 2.55, 6, and 12%, respectively for 60 days. The diets were isonitrogenous, isolipodic and the omega-3 and omega-6 requirements were satisfied. Results demonstrated that a diet with a 2.55% T. weissflogii supplement had higher percent weight gain among treatments. Although not significantly different, other parameters such as %survival, specific growth rate (SGR), protein efficiency ratio (PER), feed conversion ratio (FCR), and feed intake had desirable results in saline tilapia fed with 2.55% T. weissflogii supplement. The proximate composition of saline tilapia showed that % crude protein was high in the control group but % crude lipid was highest in the treatment 1 group. The fatty acid composition of tilapia in treatment with 2.55% T. weissflogii supplement had the highest omega-3 content at 9.29 mg/g tissue and also had the highest n3:n6 at 2.19. Muscle growth-related genes (MyoD and MYG) were upregulated while liver genes involved in long-chain polyunsaturated fatty acid synthesis (oni-fads2 and elvol5) were down-regulated in treatment groups fed with 2.55% T. weissflogii as compared to the control group. Feeding the diatom-supplemented diet to tilapia had no significant effects on hepatic cells and intestinal morphology. The results suggested that a 2.55% supplementation dose of T. weissflogii could promote growth and enhance the tissue content of omega-3 fatty acids of the seawater strain of Oreochromis niloticus.